Containers Effects on Seed Germination and Initial Growth Performance of Suregada multiflora (Ban-naringa) Seedlings: A Native Lesser Known Tree Species in Bangladesh - Dey, Soma; Hossain, Mohammed Kamal (Indian Forester, 2019)
Suregada multiflora (Ban-naringa) is an important native lesser known tree species growing in natural forests of Bangladesh. In the study, seeds were sown in polybag, seedbed and propagator house and investigated to find out the suitable media for raising quality seedlings for large scale plantation programs. Germination percentage, survival percentage, shoot length, root length, collar diameter, fresh and dry weight, leaf number were assessed for 10 months old seedlings in the nursery. Germination value, vigor index, sturdiness, volume index, root-shoot ratio, quality index were also assessed for each treatments. Seedlings raised in propagator house (T3 ) took short imbibition period (12 days) but lengthy germination period (13 days). Maximum germination and survival percentage (respectively 100% and 90%) was recorded in propagator house (T3 ) followed by 70% germination and 85.7% survival percentage in polybag (T1 ). Highest root- 1 shoot ratio (0.69) and sturdiness (77.71) was observed in polybag (T1 ). Seedlings raised in seedbed (T2 ) found maximum collar diameter, fresh and 2 dry weight, volume index and vigor index which were significantly (P<0.05) different from T1 and T3 . Growth rate was minimum in T3 and maximum in T2 treatments. Finally, polybag of size 15 Ã— 10 cm was found suitable in the nursery for quality seedling production of Suregada multiflora.